1987
DOI: 10.1121/1.394836
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of adapting components in auditory-nerve responses

Abstract: The responses of single auditory-nerve fibers of Mongolian gerbil were studied using tonal stimuli. The peristimulatory adaptation of firing rate in response to tone bursts presented in quiet and during a background stimulus is described quantitatively. The total transient response which can be produced to the onset of a tone burst, whether presented in quiet or as an intensity increment, is limited and appears to demonstrate a form of conservation. Specifically, the total numbers of spikes produced by the rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…However, a handful of AN fibers (n = 21 / 305, mostly with CFs<750 Hz) had fits with time constants below 1 ms. These values were below the PST bin width as well as the lower limits of adaptation time constants previously reported in the literature (e.g., Westerman and Smith, 1987). Typically when longer duration stimuli have been used, rapid time constants on the order of 3–4 ms and short term time constants on the order of 60 ms have been reported.…”
Section: Methodscontrasting
confidence: 60%
“…However, a handful of AN fibers (n = 21 / 305, mostly with CFs<750 Hz) had fits with time constants below 1 ms. These values were below the PST bin width as well as the lower limits of adaptation time constants previously reported in the literature (e.g., Westerman and Smith, 1987). Typically when longer duration stimuli have been used, rapid time constants on the order of 3–4 ms and short term time constants on the order of 60 ms have been reported.…”
Section: Methodscontrasting
confidence: 60%
“…In these neurons, it was possible to use a binaural stimulation paradigm that allowed separation of the adaptation of the binaural neurons from that happening at lower monaural levels, such as the auditory nerve fibers. This study revealed that these IC neurons had adaptation dynamics that were rather slow, compared with those calculated for the auditory nerve fibers (Yates et al, 1983, 1985; Westerman and Smith, 1987). The different time constants indicate that the adaptation found in the IC is different from that found in the auditory nerve, and moreover, it is not just inherited from the lower levels.…”
Section: Adaptation Becomes More Diverse Along the Auditory Hierarchymentioning
confidence: 70%
“…One possible role for adaptation in the auditory system lies in determining the sensitivity of auditory neurons to the stimulus context. The rapid adaptation in auditory nerve fiber responses (Yates et al, 1985; Westerman and Smith, 1987), and the rapid recovery from adaptation (Yates et al, 1983), suggests that the time course of adaptation in the peripheral nerve fibers might dominate the time course of adaptation in higher centers, unless it is somehow filtered out by neurons at subsequent stages. Indeed, adaptation in these early stages of the auditory pathway may have important implications in the processing of auditory cues at higher centers.…”
Section: Adaptation Of the Auditory Nerve Fibersmentioning
confidence: 99%
“…The change in neural activity is typically maximum at onset and then decays or adapts to a smaller sustained change in response. The neural mechanisms underlying adaptation have been studied in peripheral and more central stages of the auditory nervous system (e.g., Smith, 1977;Kramer and Teas, 1982;Westerman and Smith, 1987;Arehole et al, 1989;Kaltenbach et al, 1993). At the level of the auditory nerve, adaptation can be described using two time constants: "rapid", which occurs over 1-10 ms, and "short-term" in which the time constant is approx.…”
Section: Evect Of Within-train Repetition Rate On Wave Vmentioning
confidence: 99%